The impact of treasure hunt games on learning outcomes in time measurement - Martia, Liftianah Ade; Nurafni, Nurafni (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: Educational games are increasingly recognized as effective teaching tools, especially in elementary education. This study focuses on the application of a treasure hunt game in teaching mathematics, specifically time measurement concepts, to second-grade students at SD Islam PB Soedirman, Cijantung, East Jakarta.Aim: The primary aim of this research was to assess the impact of the treasure hunt game on the improvement of mathematical learning outcomes among the students.Method: This research adopted a quantitative experimental approach with a Post-test Only Control Group design. The sample consisted of 50 second-grade students divided into two groups: an experimental group (2D) and a control group (2G), each with 25 students. The experimental group was taught using the treasure hunt game, while the control group did not receive any special intervention. Data collection was conducted through observation and objective testing with 13 multiple-choice questions that had been validated. Data analysis was performed using SPSS for testing validity and reliability, as well as for prerequisite and hypothesis testing.Results: The prerequisite test results indicated that the data were homogenous and valid. The hypothesis testing, conducted using a paired t-test, showed a significant value of 0.003 (p < 0.05), indicating a significant difference between the experimental and control groups.Conclusion: Based on the findings, it can be concluded that the treasure hunt game significantly influences the improvement of mathematical learning outcomes in time measurement for second-grade students. This suggests the effectiveness of game-based learning methods in the context of elementary mathematics education.